The complete mitochondrial genome of white-tailed mole (Parascaptor leucura). Issue 3 (4th March 2021) - Xie, Fei; Chen, Dan; Qin, Boxin; Fu, Changkun; Chen, Shunde
Abstract: The white-tailed mole ( Parascaptor leucura ) belongs to genus Parascaptor, which is a monotypic genus distributed across Southwestern China, Assam (India), Bengal, and Northern Burma, and Laos. In this study, we obtained the complete mitochondrial genome of Parascaptor leucura . The genome is total 16, 875 bp in length, containing 13 protein-coding genes, 22 transfer RNA genes (tRNA), two ribosomal RNA genes (rRNA), and two non-coding regions, with a base composition of 33.5% A, 26.4% T, 25.7% C, and 14.3% G. The nucleotide sequence data of 13 protein-coding genes of P. leucura and other nine Eulipotyphla species were used to reconstruct a Bayesian phylogenetic tree. The tree shows that P. leucura belongs to subfamily Talpinae and is closely related to Scaptochirus moschatus .